2016
DOI: 10.1111/acv.12281
|View full text |Cite
|
Sign up to set email alerts
|

All roads lead to Iran: Predicting landscape connectivity of the last stronghold for the critically endangered Asiatic cheetah

Abstract: Effective conservation solutions for small and isolated wildlife populations depend on identifying and preserving critical biological corridors and dispersal routes. With a worldwide population of ≤70 individuals, the critically endangered Asiatic cheetah Acinonyx jubatus venaticus persists in several fragmented nuclei in Iran. Connectivity between nuclei is crucial for the survival of this subspecies, but detailed information to guide conservation actions is lacking. We developed a resistance surface that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 39 publications
13
49
0
Order By: Relevance
“…Most protected areas in Iran are surrounded by roads, and road mortalities are a serious threat for carnivores (Farhadinia et al., ). As suggested by Kramer‐Schadt, Revilla, Wiegand, and Breitenmoser () and Moqanaki and Cushman (), although most core patches may be potentially interconnected by dispersal (such as present study), when realistic mortality risks due to road accident and other sources of mortality are considered, most patches become functionally isolated. We identified locations where primary and secondary roads cross the predicted corridor paths between the core patches.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Most protected areas in Iran are surrounded by roads, and road mortalities are a serious threat for carnivores (Farhadinia et al., ). As suggested by Kramer‐Schadt, Revilla, Wiegand, and Breitenmoser () and Moqanaki and Cushman (), although most core patches may be potentially interconnected by dispersal (such as present study), when realistic mortality risks due to road accident and other sources of mortality are considered, most patches become functionally isolated. We identified locations where primary and secondary roads cross the predicted corridor paths between the core patches.…”
Section: Discussionmentioning
confidence: 57%
“…() and Moqanaki and Cushman (), who found that protected area status is the most important predictor of the occurrence and dispersal of African lions and Asiatic cheetah, respectively. Moqanaki and Cushman () also found corridors with high predicted connectivity rate between Abbasabad, Siyah‐Kooh and Kooh‐Bozorgi for cheetah, which are consistent with our results.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similar to the critically endangered Saharan cheetah (A. j. hecki), also living in desert habitats, the Asiatic cheetah is wide ranging and occurs at very low density compared to cheetahs in more productive habitats (Belbachir, Pettorelli, Wacher, Belbachir-Bazi, & Durant, 2015;Farhadinia et al, 2013). Although the Asiatic cheetah has been regularly reported from a number of protected areas scattered across central Iran (Hunter et al, 2007;Moqanaki & Cushman, 2016), it does not seem to be confined to these sites and has been documented to move long distances, over large stretches of deserts between distant areas (Farhadinia et al, 2013). Overall, habitat suitability criteria for the Asiatic cheetah are poorly understood, and as a corollary, the extent of environmental, biological and anthropogenic factors affecting the connectivity within this habitat and the proportion of suitable habitat receiving some level of protection are unknown.…”
Section: Introductionmentioning
confidence: 99%